2013
DOI: 10.7205/milmed-d-13-00093
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Synovial Sarcoma Treated With a Transfemoral Amputation: A Case Report and Review of the Literature

Abstract: A case of monophasic intra-articular synovial sarcoma in the right knee of a 39-year-old active duty serviceman treated with a transfemoral amputation is presented. The patient was evaluated for right knee pain and fullness. After further workup, the patient underwent computed tomography guided biopsy, with the tissue specimen consistent with intra-articular synovial sarcoma. The patient elected for a transfemoral amputation rather than limb or joint-sparing surgery. The gross specimen measured 3.5 × 3.0 × 1.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Differentiating intra-articular synovial sarcomas from benign tumors is difficult and no certain radiological features have been established. The most challenging differential diagnosis is localized PVNS [ 5 , 6 , 10 , 12 16 ]. Using multivariate data analysis this study showed that the most important variables for differentiation were size, effusion, age, and gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differentiating intra-articular synovial sarcomas from benign tumors is difficult and no certain radiological features have been established. The most challenging differential diagnosis is localized PVNS [ 5 , 6 , 10 , 12 16 ]. Using multivariate data analysis this study showed that the most important variables for differentiation were size, effusion, age, and gender.…”
Section: Discussionmentioning
confidence: 99%
“…It merely reflects the histopathological similarities to developing synovial tissue [ 5 ]. No radiological distinguishing features have been established to differentiate intra-articular synovial sarcomas from benign tumors and in the literature there are only case reports or reviews of case reports [ 5 , 6 , 12 16 ]. In this study we reviewed 7 patients with intra-articular synovial sarcomas, which is a comparatively large material of these rare tumors.…”
Section: Introductionmentioning
confidence: 99%
“…44 The majority of lower extremity synovial sarcomas arise in a PA location. 45 Three percent have been found to localize within the joint. 46 When they are discovered in an IA location, they can be difficult to distinguish from other masses including LPVNS.…”
Section: Synovial Sarcomamentioning
confidence: 99%
“…Currently, 9 cases of intra-articular SS have been reported with specific MRI findings [25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Staging Treatment and Follow-upmentioning
confidence: 99%